Spontaneous Pattern Growth on Chocolate Surface: Simulations and Experiments - Delgado, Jorge; Ferreiro-Córdova, Claudia; Gil-Villegas, Alejandro (Frontiers in Physics, 2021)
The natural variation of temperature at ambient conditions produces spontaneous patterns on the surface of chocolate, which result from fat bloom. These metastable patterns are peculiar because of their shape and cannot be obtained by controlled temperature conditions. The formation of these spontaneous grains on the surface of chocolate is studied on experimental and theoretical grounds.Three different kinds of experiments were conducted: observation of formed patterns in time, atomic force microscopy of the initial events on the grain formation and rheology of the melted chocolate. The patterns observed in our experiments follow the trends described by the Avrami model, which considers a constant value at all spatial scales of the rate of linear growth α that governs the formation of isolated grains, starting from molecular clusters. Through NVT-ensemble computer simulations, using a Kihara hard spherocylinders coarse-grained model of triacylglycerides molecules, we studied the process of nucleation that starts the pattern growth. From simulation and experiment results it is possible to derive a realistic value of α